The concepts of menopause. Part III – psychopathological approach - Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2005)
The paper – the final part of the series devoted to the concepts of menopause – presents the psychopathological approach. Using the estrogen deficiency hypothesis as the starting point the paper examines evidence for relationships between menopause, cognitive defects and depression. While some studies support the strong link between hormonal deficiency and cognitive impairment, other findings indicate the role of stress and social changes associated with aging. The links between menopause and depression are described within the framework of four hypotheses: direct effect, domino effect, psychodynamic and psychosocial. Each of them is illustrated with results of relevant studies. The author concludes that the biopsychosocial approach to mental disorders should also be applied to disorders observed during the menopausal transition.